Hospital Preparedness and Resilience in Public Health Emergencies at Royal Prima Medan Hospital - Rumi Aulia; Chrismis Novalinda Ginting; Linda Chiuman (Eduvest - Journal of Universal Studies, 2025)
Hospitals have a very important role in public health, because hospitals are places where people can get maximum health services to support the health of these patients. With the importance of the role of hospitals for the community, it is necessary to have preparedness and resilience on the part of the hospital to always be ready to receive emergencies that come from the community, such as when a disaster occurs where the role of the hospital is very important in helping victims affected by disasters. . The aim of this research is to determine the preparedness and resilience of hospitals in public health emergencies at RSU Royal Prima Medan. This type of research is quantitative research with a cross sectional approach. The population in this study was all medical and non-medical employees at RSU Royal Prima Medan, totaling 822. The sampling method used in this research was systematic sampling. The sampling technique in this research used Proportional Random Sampling so that the number of samples in this research was 134 samples. Data analysis in this study used univariate analysis. The results showed that the majority of respondents in this study were aged 36-45 years, 73 people, the majority were female, 91 people, the majority had worked < 5 years, 74 people and the majority worked as nurses, 50 people. The preparedness of RSU Royal Prima Medan in facing public health emergencies is good, the resilience of RSU Royal Prima Medan in facing public health emergencies is good.